Molecular evidence of Ebola Reston virus infection in Philippine bats - Jayme, Sarah I. (Virol J, 2015)
BACKGROUND: In 2008–09, evidence of Reston ebolavirus (RESTV) infection was found in domestic pigs and pig workers in the Philippines. With species of bats having been shown to be the cryptic reservoir of filoviruses elsewhere, the Philippine government, in conjunction with the Food and Agriculture Organization of the United Nations, assembled a multi-disciplinary and multi-institutional team to investigate Philippine bats as the possible reservoir of RESTV. METHODS: The team undertook surveillance of bat populations at multiple locations during 2010 using both serology and molecular assays. RESULTS: A total of 464 bats from 21 species were sampled. We found both molecular and serologic evidence of RESTV infection in multiple bat species. RNA was detected with quantitative PCR (qPCR) in oropharyngeal swabs taken from Miniopterus schreibersii, with three samples yielding a product on conventional hemi-nested PCR whose sequences differed from a Philippine pig isolate by a single nucleotide. Uncorroborated qPCR detections may indicate RESTV nucleic acid in several additional bat species (M. australis, C. brachyotis and Ch. plicata). We also detected anti-RESTV antibodies in three bats (Acerodon jubatus) using both Western blot and ELISA. CONCLUSIONS: The findings suggest that ebolavirus infection is taxonomically widespread in Philippine bats, but the evident low prevalence and low viral load warrants expanded surveillance to elaborate the findings, and more broadly, to determine the taxonomic and geographic occurrence of ebolaviruses in bats in the region.